Determination of organ volume using Focused Impedance Method (FIM): a simulation approach - Ahmed, Sayed Parvez; Kadir, M Abdul; Rahman, Rubina; Al-Quaderi, Golam Dastegir; Rabbani, K Siddique-e (Bangladesh Journal of Medical Physics, 2015)
A noninvasive and radiation free technique for in-vivo measurement of the volume of organs or fluids in the human body is necessary for many clinical applications. Focused Impedance Method (FIM) is a novel technique of electrical impedance measurements which has enhanced sensitivity in a localized region. FIM can sense the change in transfer impedance of an organ within a reasonable depth of the human body using surface electrodes, minimizing contributions from its neighbouring regions. This of course assumes that the impedance properties of the embedded object are different from that of its surrounding tissues. This paper presents a new method for the determination of the volume of an organ within body using dual electrode separations of a concentric 4-electrode FIM configuration. In order to develop this formalism simulated FIM measurements using surface electrodes on a cubic volume conductor with embedded spherical objects were performed using a Finite Element (FE) based simulation software, COMSOL Multiphysics®. For the present methodology, the conductivity of the object with respect to its surroundings and its depth need to be known. The former is obtainable through some primary invasive or in vivo measurements while the latter may be approximated using anatomy. Experimental results on a phantom made up of a cubic tank filled with saline showed that the proposed method can be used to determine the volume of embedded objects to an accuracy of about 5% which is adequate for most physiological measurements. The technique may also find use in geology, oceanography and industry. Bangladesh Journal of Medical Physics Vol.7 No.1 2014 24-33